Novel RSPH4A Variants Associated With Primary Ciliary Dyskinesia–Related Infertility in Three Chinese Families - Wang, Lin; Wang, Rongchun; Yang, Danhui; Lu, Chenyang; Xu, Yingjie; Liu, Ying; Guo, Ting; Lei, Cheng; Luo, Hong (Frontiers in Genetics, 2022)
Background: Radial spoke head component 4A (RSPH4A) is involved in the assembly of radial spokes, which is essential to motile cilia function. Asthenoteratozoospermia in primary ciliary dyskinesia (PCD) related to RSPH4A variants has not been reported. Materials and Methods: RSPH4A variants were identified and validated using whole-exome and Sanger sequencing in three unrelated Chinese families. High-speed video microscopy analysis (HSVA) was used to measure the beating frequency and pattern of nasal cilia of the patients and healthy control. Papanicolaou staining and computer-aided sperm analysis were applied to analyze the morphology and motility of the sperm in patient 1. Immunofluorescence was adopted to confirm the structure deficiency of sperm and nasal cilia. Results: Patient 1 from family 1 is a 22 years old unmarried male presented with bronchiectasis. Semen analysis and sperm Papanicolaou staining confirmed asthenoteratozoospermia. Novel compound heterozygote RSPH4A variants, c.2T>C / p.(Met1Thr) and c.1774_1775del / p. (Leu592Aspfs*5) were detected in this patient. HSVA showed that most of the cilia in patient 1 and patient 3 with abnormal rotational movement. Patient 2 and patient 3 are from two unrelated consanguineous family, they are both females, exhibited bronchiectasis and infertility. Two homozygous RSPH4A variant, c.2T>C / p.(Met1Thr) and c.351dupT / p. (Pro118Serfs*2) were detected respectively. Absence of RSPH4A and RSPH1 in patient 1’ s sperm and patient 3’ s respiratory cilia were indicated by immunofluorescence. Patient 2 died of pulmonary infection and respiratory failure at 35 during follow-up. Conclusion: Dysfunctional sperm flagellum and motile cilia in respiratory tract and fallopian tube were found in patients with RSPH4A variants. Our study enriches the genetic spectrum and clinical phenotypes of RSPH4A variants in PCD, and c.2T>C / p.(Met1Thr) detected in our patients may be a hotspot RSPH4A variant in Chinese.